INVESTIGATION OF CUSTOMER PERCEPTION OF VEHICLE DOOR CLOSING SOUND QUALITY - Hara, Deniz; Yağcı, Ayhan; Gürarda, Arda; Erol, Haluk (MATTER: International Journal of Science and Technology, 2017)
The perception of vehicle door closing quality is one of the most important criteria that a customer pays attention while buying a vehicle in a sales gallery. The quality perception gives a customer a clue about the general quality of the vehicle. A high quality closing sound of a vehicle door, has a potential of increasing admiration and attractiveness of the vehicle and sales volume of it. However, the quality perception has been a parameter that isn’t calculated, measured or evaluated in the design phase yet. Within this study, closing sounds and physical and acoustical parameters of the doors of a group of B and C segment vehicles are investigated and compared by handling some NVH and bench tests and jury evaluations. With the help of these study, acoustical and thus physical design parameters of a door that has high quality closing sound will be determined and will show the path to design doors that has better door closing sound quality in the further vehicle projects.